Finding The Uniqueness of Language Variations in College Students’ Speech - Gusti Ayu Mayang Priskilla Dewi (Jurnal Penelitian Mahasiswa Indonesia, 2022)
A speech community has language variations. This study aimed to investigate language variations in STMIK Jayanusa students who come from various areas. This research was qualitative research, using a case study approach. The subjects of the research were the second-year students of STMIK Jayanusa, who majored in Information Systems. Observation and field notes were used to collect the data. It was revealed that there were hundreds of language variations found among students caused by situational factors. Those situational factors were in form of the setting where the language was used, the situation or context, and the speakers of the language itself. One interesting thing from this research was an individual contributed hundreds or more language variations toward a speech community. A speech community that consists of hundreds of people will have thousands or millions of language variations. Thus, it is suggested for the next researcher who are interested to investigate the same topic to involve more subjects in his or her research so that she or he will find more uniqueness or even novel findings.